Metagenomic Analysis of Bacterial Communities and Antibiotic Resistance Genes in Penaeus monodon Biofloc-Based Aquaculture Environments - Chen, Xieyan; He, Zihao; Zhao, Jichen; Liao, Minze; Xue, Yuan; Zhou, Jianing; Hoare, Rowena; Monaghan, Sean J.; Wang, Na; Pang, Huanying; Sun, Chengbo (Frontiers in Marine Science, 2022)
Biofloc technology (BFT) is one of the most promising technologies in global aquaculture for the purpose of improving water quality, waste treatment and disease prevention in intensive aquaculture systems. However, characterisation of the microbial species and antibiotic resistance potentially present in biofloc based aquaculture environments is needed. In this study, we used high-throughput sequencing technology to comprehensively compare the bacterial communities in mariculture ponds of Penaeus monodon, by testing of water, biofloc, and the intestine of P. monodon. Operational taxonomic units (OTUs) cluster analysis showed that the 9 samples tested divided into 45 phyla and 457 genera. Proteobacteria were the dominant bacteria in water, biofloc and prawn intestine. In biofloc and intestine, the genus level accounting for the largest proportion of bacteria were Ruegeria (2.23-6.31%), with Marivita (14.01-20.94%) the largest group in water. Microbial functional annotation revealed that in all samples, genes encoding metabolism were predominant. The antibiotic resistance gene annotation showed the highest absolute abundance of patB, adeF, Oxa-243 and Brucella_suis_mprF from Proteobacteria. PatB (11.33-15.01%), adeF (15.79-18.16%), OXA-243 (35.65%) and Brucella_suis_mprF (10.03%) showed the highest absolute abundance of antibiotic resistance genes in water, biofloc, and intestines, respectively. These findings may greatly increase our understanding of the microbiota characteristics of the shrimp biofloc based aquaculture system and the complex interactions among shrimp, ambient microflora, and environmental variables. It provides a reference basis for policy on breeding environment safety and maintaining food safety in the production of Penaeus monodon.